Zbigniew Brzeziński a John Mearsheimer — dwie wizje rozwoju stosunków chińsko-amerykańskich - Kimla, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The analysis aims to show the differences in the approach to the growth of communist China as perceived by Zbigniew Brzeziński and John Mearsheimer. It shows that the distinctly different attitudes of these thinkers to China’s growth at the beginning of the 21st century were getting closer over time. It happened as a result of the evolving position of Brzeziński, who gradually realized the danger America’s consent and aid in China’s enormous economic leap poses to the United States. That is why, towards the end of his life, Brzeziński began to write about the necessity to include Russia in the political body of the West, on the condition, however, that Vladimir Putin, whose authoritarian rule aims to recreate the fascist experiment in Italy, is removed from power.
Keywords: Brzeziński, Zbigniew; Mearsheimer, John; Sino-American relations; communism; liberalism; offensive realism; evolution of Brzezinski’s position towards China; possibility of American-Chinese war